2018
DOI: 10.1534/genetics.117.300679
|View full text |Cite
|
Sign up to set email alerts
|

An Autophagy-Independent Role for ATG41 in Sulfur Metabolism During Zinc Deficiency

Abstract: 1The Zap1 transcription factor of Saccharomyces cerevisiae is a key regulator in the genomic 2 responses to zinc deficiency. Among the genes regulated by Zap1 during zinc deficiency is the 3 autophagy-related gene ATG41. Here, we report that Atg41 is required for growth in zinc-4 deficient conditions but not when zinc is abundant or when other metals are limiting. 5Consistent with a role for Atg41 in macroautophagy, we show that nutritional zinc deficiency 6 induces autophagy and that mutation of ATG41 diminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The mechanism by which autophagy protects hippocampal neurons from zinc deficiency has not yet been elucidated. A study in yeast showed that zinc deficiency caused autophagy, and genetic blockade of autophagy inhibited cellular growth [ 11 , 16 ]. Metallothioneins (MTs), proteins that bind zinc and buffer intracellular zinc levels, are degraded in lysosomes [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which autophagy protects hippocampal neurons from zinc deficiency has not yet been elucidated. A study in yeast showed that zinc deficiency caused autophagy, and genetic blockade of autophagy inhibited cellular growth [ 11 , 16 ]. Metallothioneins (MTs), proteins that bind zinc and buffer intracellular zinc levels, are degraded in lysosomes [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on zinc deficiency models without prior stress exposure to autophagy-related conditions are still lacking. We identified only two studies in yeast, which suggested that zinc deficiency induces autophagy [ 11 , 16 ]. The effect of zinc deficiency on autophagy has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…specific transporters responsible for Zn uptake into the cell and its trafficking between compartments) ( 1 ) and those for the adaptive response (which do not affect Zn availability, but help cells better tolerate the stress of Zn deficiency) ( 15 , 16 ). Adaptive response factors include enzymes that help maintain phospholipid synthesis in low Zn ( 17 , 18 ), antioxidant proteins that help ZnD cells maintain redox homeostasis ( 19 ), and factors affecting the stability of the Zn proteome ( 20 , 21 , 22 ).…”
mentioning
confidence: 99%